Gender Differences in Maladaptive Cognitive Schema in Orphans in Dakahlia, Egypt. (24th December 2013) - El-Gilany, Abdel-Hady; El-Bilsha, Mona A.; Ibrahim, Azza
Abstract : The objective of this study was to assess the gender differences of maladaptive cognitive schema among orphans in Dakahlia governorate orphanages. A cross-sectional comparative study included 152 orphan boys and 48 orphan girls in all orphanages homes in Dakahlia governorate, Egypt. Data collection tools included a structured interview questionnaire for personal data; early maladaptive schema questionnaire-short form (EMSQ-SF). The mean score of the total YSQ and all the subscales, except self-sacrifice and unrelenting standards, are significantly higher among females than males. Attention should be given to the psychological care of the orphans especially security, trust, confidence, and autonomy with more attention to orphan girls.